전문가의 일치도를 통해 알아본 중요 한증, 열증 지표 - 배광호(Kwang Ho Bae); 박기현(Ki Hyun Park); 이영섭(Young Seop Lee); 장은수(Eun Su Jang) (동의생리병리학회지, 2016)
This study intended to find out the most substantial items in cold and heat pattern identification(CHPI) questionnaire based on usual symptoms through CHPI diagnosis and evaluation by experts. 120 participants, faculties of OO university, filled out CHPI questionnaire based on usual symptoms by the way of self-reporting. Then 2 Korean Medicine doctors independently diagnosed them whether they belonged to cold pattern identification(PI) or heat PI, and scored the result of it. Pearson correlation of 2 experts was 0.649 in cold PI and 0.605 in heat PI. Agreement was 75.8%(Kappa value 0.516) in cold PI and 74.2%(Kappa value 0.465) in heat PI. Pearson correlation of 2 experts was 0.649 in cold PI and 0.605 in heat PI. Agreement between two experts was 75.8%(Kappa value 0.516) in cold PI and 74.2%(Kappa value 0.465) in heat PI. Items of high correlation with experts' evaluation followed next: "do not usually like the cold", "usually like the warm", "usually feel cold" in cold PI and "do not usually like the hot", "usually feel hot", "usually feel burning sensation in the body" in heat PI. We could infer from that facts that experts give weight on 'subjective feeling of cold or heat in participants body' and 'preference on sensation of cold and heat'. We also expect this study to be an epidemiological foundation to disclose correlation between usual CHPI and diseases.